1983
DOI: 10.1161/01.cir.67.4.907
|View full text |Cite
|
Sign up to set email alerts
|

Geometric determinants of electrocardiographic left ventricular hypertrophy.

Abstract: SUMMARY Experimental studies have suggested that electrocardiographic recognition of left ventricular hypertrophy depends on geometric relationships involving wall thickness and chamber size. To determine the clinical significance of these observations, we studied the effects of echocardiographic LV mass (LVM), posterior wall thickness (PWT), interventricular septal thickness (IVST) and internal dimension (LVID) on THE ECG is a widely used, simple and inexpensive technique, but it is unreliable in the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…In the reports on the LV mass of young adults (19-24-year-old non-athletes), the LV mass ranges from 135 to 197 g in males and from 123 to 128 g in females. [31][32][33][34][35][36][37][38] In the present study, the LV mass in boys (174.4±14.0 g) is almost equal to the results of those previous studies, but in girls the mean value of LV mass (157.4±11.1 g) is somewhat higher than that already presented. Devereux …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the reports on the LV mass of young adults (19-24-year-old non-athletes), the LV mass ranges from 135 to 197 g in males and from 123 to 128 g in females. [31][32][33][34][35][36][37][38] In the present study, the LV mass in boys (174.4±14.0 g) is almost equal to the results of those previous studies, but in girls the mean value of LV mass (157.4±11.1 g) is somewhat higher than that already presented. Devereux …”
Section: Discussionsupporting
confidence: 69%
“…Moreover, the low %fat in male subjects (40-50% less than in female) is well known and the %fat values obtained by us have been proven through our previous work not to be so different from other data presented in past reports using the same measurement method as ours. 29 The LV mass of boys has also been reported to be larger than that of girls, 30,31 but as far as we know the normal range of LV mass has not presented for adolescents, including 15-year-olds. In the reports on the LV mass of young adults (19-24-year-old non-athletes), the LV mass ranges from 135 to 197 g in males and from 123 to 128 g in females.…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, Devereux et al found that ECG voltage criteria are independent of left ventricular chamber dilatation. 22 To date, the results of such analysis for the RV has not been available. Data from our study suggest a dominant role of RVH, but not dilation, in determining the ECG voltage criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, low sensitivity of standard voltage criteria for detection of LV hypertrophy (LVH) has limited utility of the ECG for identification of patients with LVH. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Although Cornell voltage criteria modestly improve ECG detection of LVH in hypertensive patients, 6,7 the product of Cornell voltage and QRS duration (Cornell voltage-duration product), 8,9 an approximation of the area under the QRS, 10 appears to further enhance sensitivity of the ECG for LVH while maintaining high specificity. As a consequence, Cornell voltage-duration product criteria were used in combination with SokolowLyon voltage 5 to identify hypertensive patients at increased risk of subsequent cardiovascular morbidity and mortality for inclusion in the Losartan Intervention For Endpoint (LIFE) Reduction in Hypertension Study, a prospective trial designed to compare the efficacy of losartan and atenolol in reducing the risk of cardiovascular events.…”
Section: Abstract-obesitymentioning
confidence: 99%